Alih Fungsi Lahan Pertanian Ke Lahan Perumahan dan Permukiman Penduduk Dalam Perspektif Hukum Tata Ruang - Nur Iffah Maulidiyah (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTTransfer of land functions is the activity of changing the structure of order, designation, use in terms of changing the overall function of the land into the function of building structures. Transfer of land functions to changes in the age of the century has increased and decreased in terms of environmental preservation due to the demands of the needs and economic progress and knowledge. Smart policies and knowledge development in natural management are needed for the demands of protection of conservation and the resources contained in terms of preventing damage and minimizing and developing the era of civilization in developing countries and preventing disaster and changes arising from it.Keywords: land use conversion, development,ABSTRAKAlih Fungsi lahan adalah kegiatan merubah tatanan fungsi, peruntukan, penggunaan dalam hal merubah fungsi keseluruhan tanah menjadi fungsi struktur bangunan. Alih fungsi lahan pada perubahan peradabadan zaman telah meningkat dan berkurang dalam hal pelestarian lingkungan dikarenakan tuntutan kebutuhan dan kemajuan ekonomi dan pengetahuan. Kebijakan dan pengembangan pengetahuan yang cerdas dalam mengolah alam diperlukan demi tuntutan perlindungan konservasi dan sumber daya yang dikandung dalam hal pencegahan dari kerusakan dan meminimalisir serta mengembangkan era peradaban zaman negara berkembang dan pencegahan dari bencana dan perubahan yang timbul karenanya.Kata Kunci: Alih fungsi lahan, pembangunan